2018
DOI: 10.18203/2320-6012.ijrms20184043
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of carbapenem-resistant Enterobacteriaceae colonization in ICU: a pilot study from a tertiary care hospital in Western Rajasthan, India

Abstract: Background: Carbapenem-resistant Enterobacteriaceae (CRE) is a serious global public health threat. Antibiotic overuse, improper sanitation and unhygienic practices lead to large scale carriage and rapid spread.Methods: This is a prospective hospital based study planned for a period of 3 months including all patients admitted to 14 bedded Trauma ICU of a tertiary care hospital in Rajasthan. Rectal swabs were collected from admitted patients and carriage of carbapenem resistant Enterobacteriaceae looked for as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 22 publications
2
9
1
Order By: Relevance
“…Patients colonized with CRO showed increased mortality than patients not colonized with CRO (53.7%, p = 0.027). Several studies corroborate our study, showing a mortality rate ranging from 30%-75% [5,21].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Patients colonized with CRO showed increased mortality than patients not colonized with CRO (53.7%, p = 0.027). Several studies corroborate our study, showing a mortality rate ranging from 30%-75% [5,21].…”
Section: Discussionsupporting
confidence: 91%
“…The most common isolate in this study was E. coli , but carbapenemase production was maximally seen in Klebsiella pneumoniae (70.6%), followed by Pseudomonas aeruginosa (60%) and E. coli (34.6%). Our study, like other similar studies, reported K. pneumoniae the commonest carbapenemase-producing organism [ 5 , 9 , 13 - 15 ]. However, some studies reported organisms other than K. pneumoniae as a common carbapenemase producer [ 3 , 10 , 16 , 17 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Two different studies from Western Rajasthan reported 31.7% and 37% CRE respectively 11,12 . Whereas, the present study showed 14.9% CRE, this is lesser than the other two studies.…”
Section: Discussionmentioning
confidence: 98%